METHOD OF MAKING MANAGEMENT DECISION ON FINANCING THE ECONOMIC SECURITY OF ORGANIZATION - M. Vlasenko (Вестник университета)
In this article it is considered the technique of a management decision to finance the economic security of the organization, operated in a market economy. There is a dependence of the value of averted damage from resource investments in building and maintaining the desired level of economic security, in a view of this, is found their optimum value. The method takes into account a number of requirements to build economic security, which further allows you to integrate it into the overall organization of the control loop. Authors empirically obtain main obstacles which prevent a lower cost on economic security. The necessity is proved of the minimum investment in the economic security of the organization, following its creation which is inefficient.